Pathways to everyday peace: visualizing local knowledge to model system change - Panter-Brick, Catherine; Williams, Bisa; Ebnou Abdem, Aicha; Dhehby, Khadouj; Coulibaly, Yacoub; Bilal Eli, Taleb (Frontiers in Political Science, 2025)
IntroductionA critical element of peacebuilding is engaging with how different groups understand pathways to peace, yet comparative insight across social groups remains limited. We conducted research with diverse stakeholder groups in Nouakchott, Mauritania — a socially diverse society negotiating peace within a conflict-affected region — to examine how people reason about pathways to everyday peace.Methods and resultsWe used a participatory, systems mapping methodology (fuzzy cognitive mapping) to compare how people across diverse sectors of society see peace and think about pathways to everyday peace. Six focus groups included Mauritanian students, UNHCR-sponsored refugees, university professors, career diplomats, and townspeople (men and women). Each group of respondents defined everyday peace, then visually mapped key factors and perceived interconnections to describe local knowledge about pathways to peace. Three scenarios were run to visualize hypothetical interventions, modeling the relative importance of governance, socioeconomic, and community-level drivers. This study reveals important disconnects in how students, career professionals, and townspeople view pathways to everyday peace and what room exists to deliver system change.DiscussionMapping everyday peace reveals diverse forms of situated reasoning grounded in lived experience, social responsibility, and political agency. The study identifies not only how everyday peace is framed, but also how stakeholder groups evaluate room for change — what they consider actionable and where they see potential for meaningful intervention. The mapping analysis challenges assumptions of community consensus, highlighting critical blind spots and opportunities for dialogue across generations and social groups. It also offers a practical tool for civil society and state actors to clarify misalignments and develop strategies for inclusive peacebuilding efforts.